Clinical Features and Experimental Models of Cerebral Small Vessel Disease - Shindo, Akihiro; Ishikawa, Hidehiro; Ii, Yuichiro; Niwa, Atsushi; Tomimoto, Hidekazu (Frontiers in Aging Neuroscience, 2020)
Cerebral small vessel disease (SVD) refers to a group of disease conditions affecting the cerebral small vessels, which include the small arteries, arterioles, capillaries, and postcapillary venules in the brain. SVD is the primary cause of vascular cognitive impairment and gait disturbances in aged people. There are several types of SVD, though arteriosclerosis, being mainly affected by hypertension, aging, and diabetes mellitus, and cerebral amyloid angiopathy (CAA) comprise most SVD cases. The pathology of arteriosclerosis-induced SVD is characterized by fibrinoid necrosis and lipohyalinosis, while CAA-associated SVD is characterized by progressive deposition of amyloid beta (Aβ) protein in the cerebral vessels. Brain magnetic resonance imaging (MRI) has been used for examination of SVD lesions; typical lesions are characterized by white matter hyperintensity, lacunar infarcts, enlargement of perivascular spaces, microbleeds, cortical superficial siderosis (cSS), and cortical microinfarcts. The microvascular changes in the small vessels can’t be identified clinically, however, these consequent image findings can represent the SVD. There are two main strategies for prevention and treatment of SVD; i.e., pharmacotherapy and lifestyle modification. In this review, we discuss clinical features of SVD, experimental models replicating SVD, and treatments to further understand the pathological and clinical features of SVD.